1981
DOI: 10.1029/jc086ic06p05271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solar elevation and cloudiness on snow albedo at the South Pole

Abstract: Upward and downward fluxes of shortwave radiation (0.285 < h < 2.8/•m) measured at Amundsen-Scott Station (South Pole) during the summers of 1975, 1976, and 1977 are analyzed to determine effective surface albedos as functions of cloudiness (N) and solar elevation angle (•l). For nonovercast conditions (N_< 0.25) the albedo decreases linearly from 0.97 at A •< 2 ø to a minimum of 0.83 + .005 for 20 ø. With near overcast conditions (N •> 0.7), linear decrease is also found from 0.93 at •l < 2 ø to 0.84 + 0.005 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 16 publications
(13 reference statements)
6
72
0
Order By: Relevance
“…Several observational and modeling studies have found that sastrugi can cause a slight decrease in the albedo compared to flat snow (Warren et al, 1998;Carroll and Fitch, 1981;Zhuravleva and Kokhanovsky, 2011). This is due to the effective decrease in the solar zenith angle compared to the flat snow.…”
Section: Sastrugi and Brdf Of Snowmentioning
confidence: 99%
“…Several observational and modeling studies have found that sastrugi can cause a slight decrease in the albedo compared to flat snow (Warren et al, 1998;Carroll and Fitch, 1981;Zhuravleva and Kokhanovsky, 2011). This is due to the effective decrease in the solar zenith angle compared to the flat snow.…”
Section: Sastrugi and Brdf Of Snowmentioning
confidence: 99%
“…In contrast, there is no diurnal variation of albedo on cloudy days that are dominated by diffuse solar radiation, and it is thus reasonable to approximate albedo by a daily average value assuming no metamorphic changes of the snow surface microstructure during the day (Pirazzini, 2004). Albedo is also known to increase with cloud cover due to spectral variations (Brock, 2004;Carroll and Fitch, 1981;Jonsell et al, 2003;Cutler and Munro, 1996;Oerlemans and Knap, 1998). As has been noted by Warren and Wiscombe (1980) and Wiscombe and Warren (1980), the responses of all commercial pyranometers deviate from a proper "cosine law" making them usually less sensitive at large incident zenith angles.…”
Section: Albedo Over Snow and Ice Surfacesmentioning
confidence: 99%
“…In this framework Pirazzini (2004) expresses the importance of minimizing the sampling bias over sastrugi fields by collecting a large number of samples at various places or over a long time span (Carroll and Fitch, 1981) or by increasing the height of the sensor above the surface, so that the irradiance measured will also be more representative of the effective reflectance of the surface (Warren et al, 1998). For penitentes, however, the ISRT models shows that the albedo uncertainty for individual measurements still is ±0.04 at 4 m above the surface.…”
Section: Implications For Interpretation Of Albedo Measurementsmentioning
confidence: 99%
“…Firstly, sastrugis lower the averaged incidence angle, which reduces the albedo due to the strong dependence of albedo on the incidence angle of incoming radiation (Warren, 1982). This effect depends on the sun's azimuth position relative to the sastrugi axis, as perpendicular insolation results in an albedo decrease between 2 and 4 % relative to parallel insolation (Carroll and Fitch, 1981;Kuhn, 1974). Secondly, multiple reflections between the walls cause light trapping in the trough.…”
Section: Introductionmentioning
confidence: 99%